The Way of Reducing Current Values in Optical Ground Wires at Asymmetrical Faults on Overhead Transmission Lines - Egamnazarov Georgiy (Electrical, Control and Communication Engineering)
Given the fact that the installing costs of an optical ground wire on overhead lines directly depend on its cross-section, which in turn depends on the level of fault current it should withstand, in order to reduce these current values in the optical ground wire, I suggested performing its isolated descents from the end towers of the line with its transition to an optical cable. The research was carried out on the example of a 500 kV overhead line in the National Electric Power Grid. The Method of Symmetrical Components for calculating asymmetrical fault currents was not used; therefore, calculations were carried out on the base of presenting the line as a multi-wire system for the considered case as a five-wire system (optical ground wire, steel ground wire, and three phase wires). Such approach allows taking into account the initial asymmetry of the line parameters and modeling any kind of asymmetrical faults. The analyses of calculated results were performed. The conclusive evidence that the optical ground wire isolated descents from the end towers of the line give the possibility of reducing the level of maximal fault current distribution values in it and therefore its cross section, is presented.